Parent-directed marketing strategies to bridging adolescent depression stigma therapy uptake in Leyte - Estudillo, Nicole Kyla D.; Manuta, Jan Nicole; Nalda, Chaldean Joseia O.; Dacuyan, Flordeliz B. (Tacloban City Division of Management, University of the Philippines Tacloban College, 2024)
This study explores parental preferences for adolescent therapy in Leyte, Philippines, focusing on perceptions, preferred locations, financial considerations, and information sources. Using Social Marketing theory and the Marketing Mix (4Ps) framework, it aims to enhance therapy adoption and highlight parental influence in adolescent depression therapy. A mixed-method approach, integrating qualitative and quantitative methods, was employed, with data analyzed through thematic, descriptive statistics, and Likert scale analysis, compared using Convergent Parallel Analysis.
In the province of Leyte, adolescent mental health emerges as a pressing concern, yet accessing therapy services remains challenging when parents overlook these issues, this underscores the necessity for parent-focused Social Marketing interventions. Although Social Marketing interventions have proven effective in numerous health behavior change efforts, their application in this context is limited, highlighting a gap in cohesive knowledge among healthcare professionals regarding practical guidance on Social Marketing strategies.
The findings highlight the necessity of education and awareness, revealing that while parents in Leyte are aware of the benefits of therapy, they face barriers due to limited knowledge about accessing these options. A Social Marketing Mix framework was developed, emphasizing awareness and education through targeted programs, community engagement, and addressing affordability barriers.
Undergraduate thesis (Bachelor of Science in Management) -- University of the Philippines, Tacloban.
Keywords: Adolescent depression and mental health disorders -- Philippines -- Leyte; Parent-directed marketing strategies; Therapy options; Adolescent mental health; Social marketing mix